Analisis Pengaruh Kesadaran Wajib Pajak dan Pengetahuan Wajib Pajak Terhadap Kepatuhan dalam Membayar Pajak Kendaraan Bermotor (PKB) dengan Pemutihan Pajak Sebagai Variabel Moderasi di Wilayah Samsat Kota Gorontalo - Sri Susanti Tahuna; Ayu Rakhma; Nurhayati Panigoro (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to determine the effect of taxpayer awareness and taxpayer knowledge on compliance in paying motor vehicle tax (PKB) with tax relief as a moderating variable in the Samsat area of ​​Gorontalo City. The type of method used in this research is a quantitative method with data collection techniques using primary data. The number of samples in this research was 100 samples. The tool used in this research uses multiple linear regression analysis and moderation. The results of this research show that taxpayer awareness and taxpayer knowledge simultaneously influence motor vehicle taxpayer compliance in UPT. Gorontalo City Samsat. This proves that the higher the taxpayer awareness and taxpayer knowledge, the higher the taxpayer compliance, and vice versa, the lower the taxpayer awareness and taxpayer knowledge, the lower the taxpayer compliance. The tax whitening program as a moderating variable cannot moderate the influence of taxpayer awareness and taxpayer knowledge on taxpayer compliance in UPT. Gorontalo City Samsat. This proves that tax whitening can weaken taxpayer awareness and taxpayer knowledge of taxpayer compliance.